Money, Stock Prices and Central Banks A Cointegrated VAR Analysis - Wiedmann, Marcel; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD : Imprint: Physica, 2011)
This contribution applies the cointegrated vector autoregressive (CVAR) model to analyze the long-run behavior and short-run dynamics of stock markets across five developed and three emerging economies. The main objective is to check whether liquidity conditions play an important role in stock market developments. As an innovation, liquidity conditions enter the analysis from three angles: in the form of a broad monetary aggregate, the interbank overnight rate and net capital flows, which represent the share of global liquidity that arrives in the respective country. A second aim is to understand whether central banks are able to influence the stock market.
Keywords: Economics; Econometrics; Economic policy; Macroeconomics; Economics/Management Science; Macroeconomics/Monetary Economics; Finance/Investment/Banking.; Econometrics; Economic Policy